Petrographic and geochemical characteristics of magmatic rocks of the I-type Çaltı Pluton (Kemaliye, Erzincan) - Rizeli, Mustafa Eren (Gumushane University, 2025)
This research aims to reveal the geochemical characteristics and magma origin of the Çaltı Pluton located in the eastern part of the Tauride-Anatolide platform For this purpose, new interpretations were made regarding the magma source and origin, using whole-rock major oxide and trace element data of rocks representing the pluton. Stratigraphically, there are low-grade metamorphic rocks of Paleozoic-Lower Mesozoic, Upper Triassic-Upper Cretaceous allochthonous Munzur Limestones, Cretaceous ophiolitic units, Eocene Çaltı Pluton, Oligocene-Middle Miocene sedimentary rocks and Upper Miocene-Pliocene volcanic rocks. The studied Çaltı Pluton host rocks are granodiorite and granodiorite porphyry, and mafic microgranular enclaves (MMe) are monzodiorite in composition. Granodiorites and MMEs exhibit holocrystalline, and granodiorite porphyries exhibit microgranular porphyritic texture. In addition to dissolution melting textures, poikilitic textures are commonly seen in these rocks. The rocks forming the Çaltı Pluton have I type, calc-alkaline to high-K calc-alkaline properties and generally have a metaluminous character. On the primitive mantle-normalised trace element patterns, a positive correlation is observed for large ion lithophile elements (LILE) such as Rb, Ba, K and Sr and a negative correlation is observed for high field strength elements (HFSE) such as Nb, Ti, Ta, P. When the all data were evaluated, it was determined that the parent magma of the granodiorite and granodiorite porphyries of the Çaltı Pluton was formed by partial melting in the range of 1% to 3% starting from a source with phlogopite spinel-lherzolite composition representing shallow depths and that both fractional crystallization and crustal contamination played an active role in the formation of the studied rocks. © 2025, Gumushane University. All rights reserved.
I-tipi Çaltı Plütonu'na (Kemaliye, Erzincan) ait magmatik kayaçların petrografik ve jeokimyasal özellikleri
Keywords: Crustal contamination; Eocene; Fractional crystallization; I-type magmatism; Kemaliye; Petrogenesis; Çaltı Pluton